Blockchains and the economic institutions of capitalism. Issue 4 (18th January 2018) - DAVIDSON, SINCLAIR; DE FILIPPI, PRIMAVERA; POTTS, JASON
Abstract: Blockchains are a new digital technology that combines peer-to-peer network computing and cryptography to create an immutable decentralised public ledger. Where the ledger records money, a blockchain is a cryptocurrency, such as Bitcoin; but ledger entries can record any data structure, including property titles, identity and certification, contracts, and so on. We argue that the economics of blockchains extend beyond analysis of a new general purpose technology and its disruptive Schumpeterian consequences to the broader idea that blockchains are an institutional technology. We consider several examples of blockchain-based economic coordination and governance. We claim that blockchains are an instance of institutional evolution.